Air‐Processed, Stable Organic Solar Cells with High Power Conversion Efficiency of 7.41%. Issue 7 (13th January 2019) - Li, Pandeng; Mainville, Mathieu; Zhang, Yuliang; Leclerc, Mario; Sun, Baoquan; Izquierdo, Ricardo; Ma, Dongling
Abstract: High efficiency, excellent stability, and air processability are all important factors to consider in endeavoring to push forward the real‐world application of organic solar cells. Herein, an air‐processed inverted photovoltaic device built upon a low‐bandgap, air‐stable, phenanthridinone‐based ter‐polymer (C150 H218 N6 O6 S4 ) n (PDPPPTD) and [6, 6]‐phenyl‐C61 ‐butyric acid methyl ester (PC61 BM) without involving any additive engineering processes yields a high efficiency of 6.34%. The PDPPPTD/PC61 BM devices also exhibit superior thermal stability and photo‐stability as well as long‐term stability in ambient atmosphere without any device encapsulation, which show less performance decay as compared to most of the reported organic solar cells. In view of their great potential, solvent additive engineering via adding p ‐anisaldehyde (AA) is attempted, leading to a further improved efficiency of 7.41%, one of the highest efficiencies for all air‐processed and stable organic photovoltaic devices. Moreover, the device stability under different ambient conditions is also further improved with the AA additive engineering. Various characterizations are conducted to probe the structural, morphology, and chemical information in order to correlate the structure with photovoltaic performance. This work paves a way for developing a new generation of air‐processable organic solar cells for possible commercial application. Abstract : Air‐processed and highly efficient organic solar cells based on stable phenanthridinone‐based ter‐polymer (C150 H218 N6 O6 S4 ) n and [6, 6]‐phenyl‐C61 ‐butyric acid methyl ester are achieved and show superior thermal stability and photo‐stability as well as long‐term stability in ambient atmosphere. In addition, with the help of solvent additive ( p ‐anisaldehyde), the efficiency is improved from 6.34 to 7.41% and the related stability is further improved.